Analysis Of The Effect Of Tourism Development On The Development Of The Karo Regency Area - Rosari, Dina; Negara Lubis, Satia; Rujiman, Rujiman; Purworko, Agus (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2022)
Regional development is an integral part of regional planning which not only concerns the spatial planning of an area but prioritizes planning how the potential of the area can be optimally utilized for the improvement of the economic and social development of the community. One of the factors that affect the development of the region is the development of tourism. This study uses smart pls to analyze the data measurably. 1274 households made up the study population, and 304 research samples were acquired using the sample determination procedure, which employed the solving formula. Smart PLS data analysis. The study's findings demonstrated that the growth of the tourism industry simultaneously has a substantial impact on the development of the area. Three of the six independent variables—X1 (attractions), X3 (amenities), and X6 (creative economy MSMEs)—do not significantly affect the moderating variable Z (creative economy MSMEs) (comfort). The values of Tcount X1=0.819 1.96, T-count X3=0.3 79 1.96, and T-count X6=0.767 1.96 are indicative of this. Where all three variables have a T-count value smaller than the T-table (1.96). To the Karo Regency Tourism Office, it is recommended to further improve aspects related to regional development so that the development of the Karo Regency area can be maximized, especially through the tourism sector and the existence of MSMEs based on the creative economy.